Enhanced full-thickness wound healing via Sophora gibbosa extract delivery based on a chitosan/gelatin dressing incorporating microemulsion. (1st February 2021) - Shalaby, Khaled; Mostafa, Ehab M.; Musa, Arafa; Moustafa, Abd El Ghany A.; Ibrahim, Mohamed F.; Alruwaili, Nabil K.; Zafar, Ameeduzzafar; Elmowafy, Mohammed
Abstract: There are many synthetic drugs in literature have been utilized in healing of the wounds although the natural product specially antioxidants can offer similar if not better biological activity in that regard. Genus Sophora is well known to contain flavonoids and phenolic compounds which have antioxidant and inflammatory effects. So, the aim of the current study was to develop and evaluate chitosan/gelatin based Sophora gibbosa extract-loaded microemulsion as wound dressing. Sophora gibbosa extract (SGE) contained 16 major compounds which have reasonable antioxidant activity. The developed microemulsion showed that Tween 80 produced significant ( p  < 0.05) lower particle size than Pluronic F127 at the same SGE concentration whereas high concentration of extract results in large particle size. Thermodynamic stability studies showed that using higher concentration of the extract produced less stable formulations. The selected formulation was impregnated in the dressing base (chitosan/gelatin; 2:1 w/w ratio) which exhibited more water absorption. In vivo evaluation revealed that the dressing displayed superior wound repair compared to the control in terms histological examination and determination of alpha smooth muscle actin (α-SMA) and proliferating cell nuclear antigen (PCNA). Thus, SGE-loaded microemulsion-impregnated gelatin/chitosan could be a potential candidate for the wound healing.